Real-World Safety and Effectiveness of iGlarLixi in People With Type 2 Diabetes who Fast During Ramadan: Results From Wave 1 of the SOLIRAM Study - Hassanein, Mohamed (J Endocr Soc, 2021)
Background: People with type 2 diabetes (T2D) are at an increased risk of severe hypoglycaemia when fasting. SOLIRAM is an international, prospective, observational study evaluating the safety and effectiveness of the fixed-ratio combination (FRC) of insulin glargine 100 U/mL and lixisenatide (iGlarLixi) in people with T2D who fast during Ramadan. Methods: SOLIRAM will be performed in two waves. Here, we present the interim results, using descriptive statistics, from participants who fasted during Ramadan in 2020 (Wave 1). Adults with T2D who had taken iGlarLixi for ≥3 months before inclusion and who planned to fast for ≥15 days during Ramadan, were enrolled from 5 countries. During the study, iGlarLixi treatment was adjusted as per routine practice by the treating physician. Results: Overall, 155 people with T2D (54.2% male) were eligible. Mean±SD age was 58.4±9.5 years, body mass index was 30.5±6.0 kg/m² and 64.5% of people had ≥1 diabetes-related complications. Proportion of patients with ≥1 macro- and microvascular complications were 11.0% and 48.4%, respectively. Mean±SD duration of diabetes was 14.0±6.6 years and duration of iGlarLixi treatment prior to study participation was 5.7±3.3 months. Mean±SD length of fasting was 28.7±3.3 days and only 9/153 people (5.9%) broke the fast during Ramadan. Reported reasons for breaking the fast were travel, pre-existing conditions, adverse events (AEs; not related to iGlarLixi), hypoglycaemia, and menses. Change in antihyperglycaemic treatment class was minimal during the study with 79.4% and 54.2% of people taking biguanides and sulfonylureas during Ramadan, respectively. The mean±SD iGlarLixi dose changed from 24.8±11.6 U (pre-Ramadan) to 23.8±10.5 U (Ramadan period) and 24.9±11.6 U (post-Ramadan). During Ramadan, 137/153 (89.5%) and 11/153 (7.2%) of people took iGlarLixi at Iftar (evening) and before Suhur (morning), respectively. The number of participants reporting ≥1 severe and/or symptomatic documented hypoglycaemia (plasma glucose [PG] ≤70 mg/dL; primary endpoint) was 2/151 (1.3%) during pre-Ramadan, 3/148 (2.0%) during Ramadan, and none during post-Ramadan. No participant reported hypoglycaemia with PG <54 mg/dL and there were no severe or serious hypoglycaemia events. The rate of severe and/or symptomatic documented hypoglycaemia (PG ≤70 mg/dL) was 0.02 per patient-month. Improvements were observed for mean±SD HbA(1c) and fasting PG (pre-Ramadan, 8.4±1.1% and 146.9±32.1 mg/dL to post-Ramadan, 7.5±0.8% and 122.5±28.8 mg/dL) with an average reduction of -0.8±1.1% and -24.4±32.6 mg/dL, respectively. AEs were low (5.8%) and were not considered related to iGlarLixi, and there were no serious AEs. Conclusion: In a real-world setting, people with T2D treated with FRC iGlarLixi were able to fast for most of the month of Ramadan; the incidence of hypoglycaemia was low and glycaemic control was improved.